Libya and the UN : whose responsibility to protect? - Iftekhar Ahmed Chowdhury (2012)
As the blood-letting in Libya continues, and the hapless protesters battle a repressive regime that has shown no qualms to slaughter its own people, the eyes of the world are focused on the United Nations. To its credit the Security Council has acted in strong terms. Is this enough?